2007
DOI: 10.1016/j.neuroscience.2007.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Leukemia inhibitory factor participates in the expansion of neural stem/progenitors after perinatal hypoxia/ischemia

Abstract: Subsequent to perinatal hypoxia/ischemia there is an increase in the number of neural stem/progenitor cells (NSP) within the subventricular zone. Gene expression analyses have implicated Notch signaling in the expansion of these tripotential cells but there are limited data as to which signals are stimulating Notch activation. There is evidence that the LIFR/gp130 receptor heterodimer induces Notch1 to maintain NSP populations during normal development. LIF and CNTF bind to these receptor components and they c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Growth factors that are secreted by endothelial cells (Gama Sosa et al, 2007;Rosenstein and Krum, 2006) as well as by other glial cells (Aschner, 1996;Suzumura et al, 2006;Sen and Levison, 2006) during development and under pathological conditions (Ferrer et al, 1996;Lisovoski et al, 1997;Jin et al, 2002;Covey and Levison, 2007) are crucial regulators of progenitor cell mobilization. Previous reports demonstrated upregulation of several growth factors in the CC after demyelination, including HB-EGF and TGF-alpha (Ferrer et al, 1996;Lisovoski et al, 1997;Aguirre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Growth factors that are secreted by endothelial cells (Gama Sosa et al, 2007;Rosenstein and Krum, 2006) as well as by other glial cells (Aschner, 1996;Suzumura et al, 2006;Sen and Levison, 2006) during development and under pathological conditions (Ferrer et al, 1996;Lisovoski et al, 1997;Jin et al, 2002;Covey and Levison, 2007) are crucial regulators of progenitor cell mobilization. Previous reports demonstrated upregulation of several growth factors in the CC after demyelination, including HB-EGF and TGF-alpha (Ferrer et al, 1996;Lisovoski et al, 1997;Aguirre et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, LIF exerts anti-neurogenic effects in the CNS by inhibiting the terminal differentiation of murine olfactory receptor neurons as well as neurons in the primary visual cortex (Engelhardt et al, 2017; Moon et al, 2002). LIF increases neural stem cell (NSC) populations and enhances self-renewal by inhibiting differentiation, which allows NSCs to aid in neural repair during injury (Bauer & Patterson, 2006; Buono, Vadlamuri, Gan, & Levison, 2012; Covey & Levison, 2007). Using a gene microarray, Wright et al demonstrated that these anti-differentiation effects on NSC populations following LIF treatment occurred due to changes in the expression of over 200 genes (Wright et al, 2003).…”
Section: Leukemia Inhibitory Factormentioning
confidence: 99%
“…Fibroblast growth factor 2 (FGF2), epidermal growth factor (EGF), and leukemia inhibitory factor (LIF) are upregulated in the SVZ after hypoxic insult (Covey and Levison, 2007; Ganat et al, 2002; Scafidi et al, 2014). These factors promote OL generation from OPCs, as well as OL maturation and survival during normal development.…”
Section: Oligodendrocyte Regeneration In the Developing Brainmentioning
confidence: 99%